The Effect of Financial Distress and Audit Delay on Auditor Switching (Case Study of Manufacturing Companies Listed on The Indonesia Stock Exchange (IDX)) - Sembiring, Masta (Journal of International Conference Proceedings, 2023)
The aim of this study was to examine the influence of financial distress and audit delay on auditor switching in manufacturing companies listed on the Indonesian stock exchange. Data was collected through the method of document. Logistic regression analysis was applied for data analysis. This study used quantitative data obtained by BEI by observing the financial report release results of manufacturing companies listed on the Indonesian Stock Exchange. The sampling technique used was targeted sampling (opportunistic sampling method). The study found that financial difficulties had no impact on auditor changes at Indonesian Stock Exchange-listed manufacturing companies in the period 2019-2021. Audit delays will affect the turnover of auditors for manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021.Â